Emerging Innovations in Stimuli- Responsive Drug Carriers for Targeted Therapeutic Delivery (Asian Journal of Pharmaceutics (AJP), 2024)
Targeted drug delivery has revolutionized modern medicine by enabling the precise delivery of therapeutics tospecific sites while minimizing systemic side effects. This comprehensive review explores recent advancementsin targeted drug delivery systems, focusing on nanotechnology-based approaches, stimuli-responsive carriers,and innovative targeting strategies. Nanoparticles, including liposomes, polymeric nanoparticles, and inorganicnanoparticles, offer enhanced drug solubility and targeted delivery to specific tissues or cells. Stimuli-responsivedrug carriers respond to environmental cues, allowing for controlled drug release. Targeting strategies employligands to bind to receptors on target cells, enabling precise delivery of therapeutics. Applications span variousdiseases, including cancer, neurological disorders, infectious diseases, and chronic conditions. Despite challengessuch as biocompatibility and regulatory considerations, targeted drug delivery holds promise for personalizedmedicine, improving therapeutic efficacy, and patient outcomes.